2008
DOI: 10.1007/s00442-008-1063-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of C4 grass introductions on soil carbon and nitrogen cycling in C3-dominated successional systems

Abstract: While recent research has focused on the effects of exotic plant species on ecosystem properties, less is known about how restoring individual native plant species, differing in biomass and tissue chemistry, may impact ecosystems. We examined how three native C(4) prairie grasses affected soil C and N cycling 11 years after reintroduction into successional old-field communities dominated by non-native C(3) grasses. The species examined in this study differ in traits that are expected to influence soil C and N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 51 publications
5
44
2
Order By: Relevance
“…Dickson and Wilsey (2009) also found that both litter quality and microclimate affected decomposition rates of prairie species. The surface soil temperature differences were expected based on the relatively small amount of surface litter and shoot biomass associated with the old-field species relative to A. gerardii (Mahaney et al 2008). Eviner (2004) found that species had a large influence on soil temperatures, with both lower daily fluctuations in plots with higher graminoid shoot biomass and litter, and a negative correlation between summer afternoon temperatures and litter quantity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dickson and Wilsey (2009) also found that both litter quality and microclimate affected decomposition rates of prairie species. The surface soil temperature differences were expected based on the relatively small amount of surface litter and shoot biomass associated with the old-field species relative to A. gerardii (Mahaney et al 2008). Eviner (2004) found that species had a large influence on soil temperatures, with both lower daily fluctuations in plots with higher graminoid shoot biomass and litter, and a negative correlation between summer afternoon temperatures and litter quantity.…”
Section: Discussionmentioning
confidence: 97%
“…Andropogon gerardii and the old-field species differ widely in the amount and chemistry of tissue they produce (Baer et al 2002;Camill et al 2004;Craine et al 2002b;Mahaney et al 2008;Tjoelker et al 2005;Wedin and Tilman 1990). In a related study comparing the effects of native prairie grasses and these old-field grasses on soil carbon (C) and nitrogen (N) cycling, Mahaney et al (2008) found no significant differences between B. inermis and E. repens surface litter, shoot biomass, or green tissue chemistry (C:N or acid detergent fiber (ADF): N), suggesting that these species would have similar effects on soil processes. Indeed, Mahaney et al (2008) found that soils under A. gerardii, with 5 to 6-fold greater shoot biomass and more recalcitrant tissue (higher C:N, ADF:N), tended to have slightly slower N cycling rates and significantly greater surface litter accumulation (3-4 times higher) than soils under the old-field grasses.…”
Section: Study Speciesmentioning
confidence: 98%
“…higher C:N and lignin:N ratios) than C 3 grasses and forbs (Baer et al, 2002;Wedin and Tilman, 1990). Consequently, increasing dominance of C 4 species generally decreases N and C mineralization rates (Baer et al, 2002;Epstein et al, 1998;Mahaney et al, 2008). In contrast, C 3 forbs have deeper roots and take up more water and nutrients (Nippert and Knapp, 2007) and accumulate N and C deeper in the soil layers compared to C 4 grasses (Fornara and Tilman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Minnesota USA indicate high-diversity mixtures of both C 3 and C 4 stored 500% and 600% more soil C and N than did monoculture plots of the same species (Fornara and Tilman, 2008). Thus, mixes of C 3 and C 4 species in PVS within crop fields should increase SOC stocks and the accompanying stoichiometric sink for N (Barrett and Burke, 2000;Fornara and Tilman, 2008;Mahaney et al, 2008;Ramundo et al, 1990) when C accumulates more rapidly than N. Additionally, management practices such as annual burning and mowing can affect prairie vegetation composition (ratio of C 3 to C 4 plant species) and influence N and C cycling in RNP and PVS (Collins et al, 1998). For example, although mowing and burning influencing the presence of forbs, burning declined plant richness (Carter et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We cold-stored the soil and then oven-dried it at 65°C (149°F) for 48 hours to prevent loss of N at higher temperatures (Mahaney et al 2008). We weighed soil before and after drying and divided the dry weight by the volume of the core to determine soil bulk density.…”
Section: Journal Of Soil and Water Conservationmentioning
confidence: 99%